A comparative study of intrathecal isobaric ropivacaine and hyperbaric bupivacaine for elective lower segment caesarean section - Ramarao, M.; Laxman Rao, K.; Santhi Sree, M.; Raghuvardhan, M. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: The study was to compare intrathecal isobaric ropivacaine and hyperbaric bupivacaine in terms of onset of sensory block, maximum height of sensory block, total sensory duration, onset of motor block, degree of motor block and duration of motor block, quality of anesthesia. Methods: The 100 cases of ASA II undergoing elective lower segment caesarean section were taken for the study and divided into two groups. Group B patients received 2 ml of hyperbaric bupivacaine intrathecally. Group R patients received 2ml of isobaric ropivacaine intrathecally. Patients were evaluated for onset and duration of sensory block, onset and duration of motor block, maximum height of sensory block, quality of anaesthesia, time to request for analgesia, hemodynamic parameters and side effects if any were studied. Results: There were no significant differences between the two groups in mean time to onset of sensory block. Maximum sensory height attained in group B ranged between T4 and T6, where as in group R, it ranged between T2 and T6 which was clinically and statistically highly significant (p<0.001). Total duration of sensory block in group B and in group R, which is not significant (p=0.068). Mean time onset of motor block was 4min in group B and 8 min in group R, (p<0.001). Duration of motor block was 155.20±14.95 min in group B and 94.10±8.31 min group R, which is clinically and statistically significant (p<0.001). Conclusions: Ropivacaine 15 mg (2 ml of 0.75% isobaric ropivacaine) provides comparable quality of sensory block but has slower onset and significantly shorter duration of motor block compared to bupivacaine.